2013
DOI: 10.5923/j.ijmb.20120205.03
|View full text |Cite
|
Sign up to set email alerts
|

The Spectrum of Infections by <i>Fusarium</i> Species on <i>Codiaeum Variegatum</i> (L.) Blume Cultivars as Influenced by Fructose Specific Lectin

Abstract: This study sought to have an insight into the mechanism of action of diseases responsible for the susceptible Codiaeum variegatum (garden croton) leaves induced by Fusarium species and the clinical importance of the d isease resistant types. The plants were obtained fro m the Babcock University Germp lasm Repository. Therefore, phytopathogenic Fusarium species were isolated fro m three diseased susceptible cult ivars of C. variegatum (ovalifolium, royal-like and punctatum). Accordingly, lect in was isolated, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
1
1
0
Order By: Relevance
“…This is slightly similar to the lectin extracted from Codiaeum variegatum [29]. Lectin in this study was found to be heat stable from 20˚C to 30˚C and the heat stability began to decrease at 40˚C and completely lost its activity at 70˚C.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…This is slightly similar to the lectin extracted from Codiaeum variegatum [29]. Lectin in this study was found to be heat stable from 20˚C to 30˚C and the heat stability began to decrease at 40˚C and completely lost its activity at 70˚C.…”
Section: Discussionsupporting
confidence: 80%
“…As shown in the result virtually all the lectins from the various strains of Schizophyllum commune are Mannose binding. This type of lectin is quite different from the recently reported Lectin [29]. As known they have attracted great interest due to their various biological activities, such as antitumor [30] [31].…”
Section: Discussionmentioning
confidence: 85%